2020
DOI: 10.3791/61148
|View full text |Cite
|
Sign up to set email alerts
|

Production of Germ-Free Fast-Growing Broilers from a Commercial Line for Microbiota Studies

Abstract: Studies of the gut microbiota contribution to the host physiology and immunocompetence are facilitated by the availability of germ-free animal models, which are considered the gold standard. Nesting birds are ideal models for the production of germ-free animals since there is no need to raise their relatives under sterile conditions. Germ-free chickens are mainly generated from specific-pathogenfree (SPF) experimental lines, which are poorly representative of commercial chicken lines. The method proposed here … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 5 publications
(8 reference statements)
0
17
0
Order By: Relevance
“…To study the effect of the microbiota on E. tenella infection, we used an original model of germ-free broilers that we recently developed in our facilities ( Guitton et al., 2020 ). A previous study reported that a high dose of E. tenella inoculum administered per os (>10,000 sporulated oocysts) led to similar oocyst load in caecal contents in germ-free and conventional chickens ( Visco and Burns, 1972a ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To study the effect of the microbiota on E. tenella infection, we used an original model of germ-free broilers that we recently developed in our facilities ( Guitton et al., 2020 ). A previous study reported that a high dose of E. tenella inoculum administered per os (>10,000 sporulated oocysts) led to similar oocyst load in caecal contents in germ-free and conventional chickens ( Visco and Burns, 1972a ).…”
Section: Discussionmentioning
confidence: 99%
“…Conventional and germ-free Ross PM3 broilers were hatched in the Infectiology of Farm, Model and Wildlife Animals Facility (PFIE, Centre INRAE Val De Loire: ; member of the National Infrastructure EMERG’IN) as described by ( Guitton et al., 2020 ). Briefly, Ross PM3 eggs from two French farms were collected, decontaminated with a 1.5% peracetic acid solution (1.5% Divosan Plus VT53, Johnson Diversey, France).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, the color of the broth media changed to red in the presence of resazurin, a redox indicator of FTM, indicating that the microorganisms were cultured in the aerobic incubation conditions. [ 30,31 ]…”
Section: Resultsmentioning
confidence: 99%